PENERAPAN FUNGSI PRODUKSI COBB-DOUGLAS GUNA MENGANALISIS PROSES TRANSFORMASI DALAM SISTEM PRODUKSI - Sodikin, Imam; Sarsito, Bambang Mudo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
Simply production system can be described as a relation usher the input element, process and input. The element have to be supported with the feed back to control the system produce that to be able to improve the continuous repair. PT. Barata Indonesia in the early year 2003 was doing program to improve of output by performing variously repair of the task department. From the repair result will be was done by a measurement with to compare with the production process previous period. In this research, the method used is function produce of the Cobb-Douglas by using of software SPSS analysis. From data processing result, got an equation of linear regression which have transformed into function produce the following Cobb Douglas: For the year of 2002 equation is Q = 90,92.I10,75.I40,53 and for the year of 2003 Q = 79,04.I10,66.I40,39. Based of the result analyze by using the function produce the Cobb-Douglas have given is Return to scale ( RTS) with the value 1,28 for the year of 2002 and 1,05 for the year of 2003. Because value RTS > 1 so this matter is inferential that production process of two period known of the Increasing to Scale, meaning that proportion of factors of production, such as input will be increase the production the larger ones. While for the calculation of elasticity given the following value: Year 2002 raw material elasticity = 0,75%, meaning each every addition 1% raw material by use of constant machine man hours, product become will increase 0,75%, for the elasticity of use of machine man hours = 0,53% meaning each every accretion 1% machine man hours by use constant raw material, will increase the product addition become equal to 0,53%. Year 2003 raw material elasticity = 0,66%, meaning each every addition 1% raw material by use of constant machine man hours, product become will increase 0,66%, for the elasticity of use of machine man hours = 0,39% meaning each every accretion 1% machine man hours by use constant raw material, will increase the product addition become equal to 0,39%.